Morphology, mechanical properties, and biodegradability of all‐cellulose composite films from oil palm empty fruit bunch. (12th August 2020) - Zailuddin, Nur Liyana Izyan; Osman, Azlin Fazlina; Rahman, Rozyanty
Abstract: Palm oil plantations are very important in that they supply vegetable oil globally. However, increased production of palm oil prompts the accumulation of large lignocelluloses residues in the form of oil palm empty fruit bunch (OPEFB). This study explored the advantages of using OPEFB in the production of all‐cellulose composite (ACC) films. The isolation process of the raw OPEFB fiber was carried out using a chemical process to extract OPEFB nanocellulose. ACC films from OPEFB and microcrystalline cellulose (MCC) were prepared using a dimethylacetamide (DMAC) and lithium chloride solvent system whereby the partially dissolved cellulose was transformed into the matrix phase surrounding the remaining nondissolved fiber. ACC films with 1% (wt/vol) OPEFB and 3% (wt/vol) MCC were prepared and the effects of chemical treatment of the OPEFB cellulose on the mechanical properties, crystalline structure, morphology, moisture absorption and soil biodegradability of the ACC film were investigated. The tensile strength of the ACC film was tremendously improved by chemical treatment. For instance, when acetic acid was used to treat the nanocellulose, the resultant film showed 279% increment in tensile strength value. However, formic acid‐treated films demonstrate greater moisture uptake and soil biodegradation rate. The findings could be related to the alterations of hydroxyl group composition in the nanocellulose and variation in dissolution rate of the nanocellulose during chemical treatment. Abstract :